2007
DOI: 10.1128/iai.00411-07
|View full text |Cite
|
Sign up to set email alerts
|

Additive and Synergistic Bactericidal Activity of Antibodies Directed against Minor Outer Membrane Proteins of Neisseria meningitidis

Abstract: Neisseria meningitidis serogroup B is a major cause of bacterial meningitis in younger populations. The available vaccines are based on outer membrane vesicles obtained from wild-type strains. In children less than 2 years old they confer protection only against strains expressing homologous PorA, a major, variable outer membrane protein (OMP). We genetically modified a strain in order to eliminate PorA and to overproduce one or several minor and conserved OMPs. Using a mouse model mimicking children's PorA-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 47 publications
5
80
0
Order By: Relevance
“…Previous studies indicated that for antibodies directed at "minor" protein antigens, a critical density of immune complexes on the bacterial surface was required to elicit bactericidal activity, and this threshold was reached only when more than one minor antigen was targeted (47). Evidence for cooperative serum bactericidal activity between antibodies to fHbp and Neisseria heparin binding antigen in adults immunized with a multicomponent recombinant vaccine was also recently reported (43).…”
Section: Resultsmentioning
confidence: 89%
“…Previous studies indicated that for antibodies directed at "minor" protein antigens, a critical density of immune complexes on the bacterial surface was required to elicit bactericidal activity, and this threshold was reached only when more than one minor antigen was targeted (47). Evidence for cooperative serum bactericidal activity between antibodies to fHbp and Neisseria heparin binding antigen in adults immunized with a multicomponent recombinant vaccine was also recently reported (43).…”
Section: Resultsmentioning
confidence: 89%
“…Note that in our previous study, the binding of anti-fHbp MAbs to the bacterial surface was saturated through a wide range of MAb concentrations (29). Further, binding by an individual MAb did not result in sufficient immune complex to engage C1q and activate classical complement pathway bactericidal activity (18,30). However, if the amount of immune complex was increased on the bacterial surface by the binding of two anti-fHbp MAbs, or by binding by an individual antifHbp to a mutant strain of a strain that naturally expresses a low level of fHbp that was engineered to have increased expression of fHbp, there was an activation of the classical complement pathway and bacteriolysis (28).…”
Section: Discussionmentioning
confidence: 99%
“…If antibodies of two different specificities are involved, the removal of either of these antibody specificities could potentially result in loss of bactericidal activity. The cooperative (even synergistic) action of antibodies to two different OMPs has been reported (57). Certainly, LPS is often closely associated with outer membrane proteins, so it would not be hard to imagine cooperation in killing between bactericidal antibodies specific for LPS and OMPs.…”
Section: Discussionmentioning
confidence: 99%